2020
DOI: 10.1039/d0ta02198a
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite ferroelectric thin film as an efficient interface to enhance the photovoltaic characteristics of Si/SnOx heterojunctions

Abstract: Ferroelectric thin layer as an interface to enhance the photovoltaic characteristics of Si/SnOx heterojunctions for building efficient ferroelectric-based solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 41 publications
6
19
0
Order By: Relevance
“…The O 1s peak is deconvoluted into three peaks at 530.16 ± 0.051 eV (associated with O–Sn 2+ ), 530.80 ± 0.05 eV (associated with O–Sn 4+ ), and 532.13 ± 0.05 eV (absorbed O x ions), as shown in Figure d . The contents of SnO 2 and SnO were calculated using the Sn 3d spectra and were 48 and 52%, respectively, which suggest a p-type SnO x film . This result is also in good agreement with our previous X-ray diffraction (XRD) studies that confirmed the presence of both phases .…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The O 1s peak is deconvoluted into three peaks at 530.16 ± 0.051 eV (associated with O–Sn 2+ ), 530.80 ± 0.05 eV (associated with O–Sn 4+ ), and 532.13 ± 0.05 eV (absorbed O x ions), as shown in Figure d . The contents of SnO 2 and SnO were calculated using the Sn 3d spectra and were 48 and 52%, respectively, which suggest a p-type SnO x film . This result is also in good agreement with our previous X-ray diffraction (XRD) studies that confirmed the presence of both phases .…”
Section: Resultssupporting
confidence: 91%
“…The decreased value for Δ E V is related to the formation of a ZnO/SnO 2 heterojunction, as Figure suggests, since the SnO x film is composed of SnO and SnO 2 . The Δ E C at the interface was also determined from the following equation , where E g SnO x and E g ZnO are the band gap values obtained experimentally for the SnO x ( E g = 2.70 eV) and ZnO ( E g = 3.37 eV) films, which agrees with the calculated ones. The Δ E C is 0.98 eV.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations